The three escapes of Hannah Arendt : a tyranny of truth - Krimstein, Ken. (London : Bloomsbury Publishing, 2018)
Provides an illustrated biography of Hannah Arendt, one of the most prominent philosophers of the twentieth century, a hero of political thought, and a complex, controversial, deeply flawed, and courageous woman. Her intelligence and "virulent truth telling" led her to insights into the human condition, and her experience continues to shine a light on how to live as an individual and a public citizen in troubled times. --Adapted from publisher description
Includes bibliographical references.
Donated by Farhana Zahir, Assistant Professor, BRAC Business School, BRAC University
Keywords: Arendt, Hannah, -- 1906-1975 -- Comic books, strips, etc; Philosophers -- Biography -- Comic books, strips, etc; Jewish philosophers; Graphic novels; Biographical comics